SISTEM INFORMASI PENJUALAN BERBASIS DEKSTOP STUDI KASUS TOKO FORTUNER GORONTALO - Sidik, Zainudin; Ismail, Abdul Rahman (Journal Of Software Engineering And Communication, 2025)
All activities that take place in the Fortuner store, whether related to service or the sale of spare parts, still rely on small notes, the data recording system currently used in this Fortuner store can be considered conventional. There are many types of motorcycle spare parts offered, and the increase in the number of buyers can cause employees serving customers to experience difficulties in managing and calculating transactions quickly and accurately. Additionally, if there is a large amount of data, the data entry process becomes slow, which can later affect the preparation of reports. The goods transaction process in the Fortuner store relies solely on temporary receipt transaction evidence, which often leads to data errors or misplaced receipts due to the high number of consumers visiting. This study uses a descriptive methodology, where information is collected from the sales system and document records, analyzed, and then converted into a desktop application using the waterfall model for software design and development. The two types of application user developed are the admin level (for processing and transaction) since the cashier is the shop owner, and the consumer level (for ordering). The application is created using the Visual Basic programming language, with several plugins added to enhance the application display. The database is stored using MySql. The results of implementing this application include the ability to produce required reports quickly, a summary of goods data, more accurate transaction data based on stock, and a faster service and sales process for each consumer, with a duration of 5 to 10 minutes depending on the goods ordered.